Strategi Pelatihan Bahasa Arab dengan Metode Debat bagi Mahasiswa Komunitas Al-Kindy di Pusat Ma’had Al-Jaami’ah UIN Maulana Malik Ibrahim Malang - Agung Muttaqien; Faedurrohman Faedurrohman (Al-Muyassar: Journal of Arabic Education, 2022)
Arabic debate is one of the highest components of the art of speaking (maharah kalam) in learning. This activity also trains students in addition to Arabic language knowledge but also trains in arguing, studying, various kinds of perspectives. Based on a wide variety of knowledge and sharp analysis of phenomena. So that every Debate title is issued. Of course there are problems that are solved through various points of view, for example in terms of economy, education, social, culture and others. This study uses a qualitative approach with a descriptive method. The purpose of this study was to determine the Arabic debate training strategy for Al Kindy students at the Mahad Al Jami'ah Center of UIN Maulana Malik Ibrahim Malang. Therefore, it has a strategic-systematic way of arguing that is built to be accepted, until it is implemented. Of course it has a maximum preparation process so that it can be realized. The following are the stages of the debate training: (1) Before starting the exercise, students are given various information about the exercise and are called to prepare several arguments and data sources related to the title of the debate raised,(2) The process of cross-member discussion/study does not just flow, but there are presenters who are scheduled to take turns, he is responsible for the flow of discussions or studies related to current topics and issues led by a moderator and concluded with the minutes, (3) The practice of practicing direct Arabic debate, using two ASEAN Parliamentary systems consisting of two teams of three people each. And the British Parliamentary system consists of four groups, namely the agree group 1, the agree group 2, the contra group 1, the contra group 2, each group consists of two people.